Hermeneutic phenomenological research method simplified - Kafle, Narayan Prasad (Bodhi: An Interdisciplinary Journal, 2013)
This write-up aims to first clarify the notion of phenomenology by offering sayings of different experts of this genre. Thereafter, it attempts to briefly trace its genesis and classify this broad idea in three different schools viz. transcendental, hermeneutic and existential. After discussing very precisely on each of these schools, it focuses on the premises of hermeneutic phenomenology as a method for doing research. The purpose of this essay is to collect and exhibit a crude paradigmatic clue of doing a hermeneutic phenomenological research. During the course, it emphasizes on the metaphysical stance, methodological grounds, quality concerns and ethical issues that contribute to its paradigmatic assumptions. Bodhi: An Interdisciplinary Journal, 5, 2011, Page 181-200 DOI: http://dx.doi.org/10.3126/bodhi.v5i1.8053